Gambaran pengetahuan dan sikap dosen Fakultas Peternakan UNSRAT Manado terhadap kekerasan dalam rumah tangga - Kaunang, Andreas P.; Ratag, Gustaaf A. E.; Sapulete, Margareth (UNIVERSITAS SAM RATULANGI, 2016)
Objective: To determine the knowledge and attitude of lecturers in Faculty of Animal Husbandry of Sam Ratulangi University toward domestic violence. Method: This research used a grounded theory approach. Data wass collected through focus group discussion by taking 12 informants and then we selected five informants purposefully for an in-depth interview. Results: Majority of informantsâ€™ knowledge in domestic violence is good enough. Most informants are concerned about the increase of domestic violence cases in Indonesia and would advise the victim to perform a penal mediation before taking legal action. Conclusion: Lecturerâ€™s role in preventing domestic violence can begin with providing exemplary behaviors in daily life and outlines the university â€œTri Dharmaâ€ principles through education, research and community service. Keywords: Lecturersâ€™ knowledge, lecturersâ€™ attitude, domestic violence